Parenting Style and Emotional Distress Among Chinese College Students: A Potential Mediating Role of the Zhongyong Thinking Style - Hou, Yanfei; Xiao, Rong; Yang, Xueling; Chen, Yu; Peng, Fei; Zhou, Shegang; Zeng, Xihua; Zhang, Xiaoyuan (Frontiers in Psychology, 2020)
Previous studies suggested that parenting style was associated with college student′s emotional distress. However, little is known about the underlying mechanisms underlying this relation in Chinese culture. The present study investigated the associations between parenting style and college student′s emotional distress (depression and anxiety symptoms), examined the mediating effects of Confucian personality－Zhongyong thinking, and explored whether gender, age, and socioeconomic status (SES) moderated the direct and/or indirect effects of parenting style on emotional distress. Results from a large representative sample of Chinese college students (n=3943) indicated that (a) parental rejection and overprotection was positively and mildly associated with depressive and anxiety symptoms and negatively and mildly related to Zhongyong thinking. Parental warmth significantly correlated with the three variables in the opposite direction; Zhongyong thinking correlated negatively and moderately with depression, and mildly with anxiety; (b) Zhongyong thinking partially mediated the associations of parental rejection and warmth with emotional distress. Specifically, to the extent that students perceived less rejection and more warmth, they were more likely to develop Zhongyong thinking associated with decreased emotional distress; (c) gender and SES moderated the association between parenting style and Zhongyong thinking. Specifically, for students with low SES, the negative relationship between parental overprotection and Zhongyong thinking was stronger; for males and high SES students, the positive link between parental warmth and Zhongyong thinking were stronger. Results highlight the importance of researching potential effects of college student′s Zhongyong thinking within the family system in Chinese culture.